Biochemistry - Champe, Pamela C Harvey, Richard A Ferrier, Denise R (Lippincott's illustrated reviews., 2005)
"Now in full color, Lippincott's Illustrated Reviews: Biochemistry, Third Edition, enables rapid review and assimilation of large amounts of complex information about the essentials of medical biochemistry. As in previous editions, Lippincott's Illustrated Review: Biochemistry features an outline format, over 600 illustrations, cross-references to other titles in the series and over 100 USMLE-style questions." "Students who are preparing for standard courses or examinations (USMLE, COMPLEX, ECFMG) will find this work "must read" material to master biochemistry essentials."--Jacket.